Resilience of Transport Infrastructure Systems - LeviÃ¤kangas, Pekka; Aapaoja, Aki (Universitas Indonesia, 2015)
This paper proposes a generic resilience framework that is applied to transport infrastructure systems. The framework is based on prior research and literature material on resilience. The paper first reviews some of the relevant literature and builds a resilience model that distinguishes the attributes and sub-attributes of resilience. Then the resilience model and transport system components are merged into single system resilience matrix. The complexity of resilience of a meta-system – a system comprising several sub-systems – is underlined. Finally, the implications on other meta-systems, for example those governed by cities and municipalities, are briefly discussed. In fact, cities and municipalities face even a more complex resilience analysis tasks than do the state authorities who mostly govern sector systems (e.g. transport) within their mandate.